Chemical and toxicological characterisation of residues from offshore in-situ burning of spilled fuel oils. (2022) - Faksness, Liv-Guri; Altin, Dag; Dolva, Hilde; Nordtug, Trond
Highlights: Chemistry and acute toxicity (early life stage of C. finmarchicus ) in LE-WAF of unburned and burned ULSFO, IFO180 and MGO . WAFs of ISB residues seem to be less acute toxic than WAFs of initial unburned oils. Predicted toxic units indicate that the PAHs seem to contribute most to the toxicity. The burns reduced the total mass of PAH by >90 % compared to the released, unburned oils. Potential impact of ISB depends on e.g. burn efficiency and residue properties. Abstract: Burn residues collected after large scale experimental in situ burns performed in the North Sea were characterised with emphasis on chemistry and acute toxicity. Low-energy water accommodated fractions (WAFs) of three marine fuels (Ultra Low Sulphur Fuel Oil (ULSFO), bunker oil (IFO180), and marine gas oil (MGO) and their field-generated residues from in situ burning (ISB). were prepared to evaluate the potential impact of ISB residue to the environment. The toxicity effects on primary consumers were assessed by testing on early life stage (nauplii) of the marine copepod Calanus finmarchicus . Toxicity studies showed that ISB decreased the acute toxicity of the WAFs compared to the initial oils. WAF of MGO had highest toxicity, and ISB residue of MGO seems to be more toxic than WAFs of fresh ULSFO and IFO180. Additive toxicity expressed as toxic unit (TU) based on the chemical composition also indicated that the toxicity of WAFs from ISB residues were lower than for the initial oils. The 2−3 ring PAHs seem to contribute most to the TU. Overall, the three offshore burns reduced the total mass of PAHs in the water accommodated fractions by >90 % compared to the released unburned oils and caused a reduction of the acute toxicity to copepod nauplii.